PENGARUH KOMPRES DAUN MELATI TERHADAP JUMLAH LEUKOSIT PADA BENDUNGAN ASI - Suryanti, Yuli; Faulia Mauluddina; Sri Emilda (LPPM STIKes Mitra Adiguna, 2024)
Breast milk dams occur on the 2nd – 10th day after giving birth, which is characterized by redness, heat, pain, swelling and increased body temperature, which is a sign of inflammation. Leukocytes are white blood cells produced by hemopoietic tissue in the body’s defense system against infection. The aim of this research is to determine the effect of administering jasmine leaf compresses on the number of leukocytes in breastfeeding mothers with breast milk. This type of research uses Quasy Experimental with pretest and posttest design with control group. This research was divided into two groups, namely the group that was given jasmine leaf compress treatment with 15 respondents and the breast milk control group with 15 respondents. The instrument used for blood leukocyte counts uses the Hematology Analyzer Method using the BC-3000 Plus (Automatic Analyzer) and Numeric Rating Scale (NRS) and SPES (Six Point Engorgement Scale). The results of the study showed that there was a significant effect between the pain intervention group given jasmine leaf compresses on the number of blood leukocytes in breast milk dams with a p value = 0.001. Mothers who experience breast milk dams are given a jasmine leaf compress by placing jasmine leaves on the swollen breasts for 1-2 hours or until the leaves wilt. The conclusion of this study is that there is an effect of jasmine leaf compresses on reducing the number of blood leukocytes in the group of breast pain and swelling with breast milk dams. Keywords: Jasmine leaf compress, breast milk dam, leukocyte count